Biomechanical restoration of metastatic cancer-induced peri-acetabular bone defects by ablation-osteoplasty-reinforcement-internal fixation technique (AORIF): To screw or not to screw?. (February 2022) - Morris, Montana T.; Alder, Kareme D.; Moushey, Alexander; Munger, Alana M.; Milligan, Kenneth; Toombs, Courtney; Conway, Devin; Lee, Inkyu; Chen, Fancheng; Tommasini, Steven M.; Lee, Francis Y.
Abstract: Background: Minimally invasive percutaneous polymethyl methacrylate cement augmentation procedures offer numerous clinical advantages for patients with periacetabular osteolytic metastatic bone defects in contrast to open reconstructive procedures that are associated with many complications. Several techniques, such as Ablation-Osteoplasty-Reinforcement-Internal Fixation (AORIF), cementoplasty alone, and screw fixation alone are currently used. There is no consensus on optimal skeletal reinforcement of diseased bones. The purpose of this study was to determine the most effective technique of percutaneous acetabular augmentation for joint preservation, with respect to resilience on cyclic loading and fracture pattern at maximal load to failure. Methods: Five cohorts of hemipelvis composite bones with uniform periacetabular defects and various types of reinforcement techniques were utilized to simulate osteolytic metastasis in the weight bearing dome of the acetabulum. Five groups of hemipelves underwent finite element analysis and biomechanical testing for load to failure, energy absorption to failure, stress relaxation on cyclic loading, and fracture locations. Results: The combination of screws and bone cement augmentation demonstrated significant higher energy absorption than the cement or screw only groups ( p < 0.05), and better protection of acetabulum from displaced intraarticular fractures than the screws alone oror cement only groups ( p < 0.05). Resilience to cyclic loading was higheest in the screw with cement fixation group than the screw only repair ( p < 0.01), though not the cement fixation only group. Interpretation: These data support the hypothesis that cementoplasty combined with screw augmentation such as the AORIF technique provides the best protection of acetabulum from massive metastatic cancer-induced acetabular fractures compared to augmentation with screws or cement alone. Highlights: Effects of screw reinforcement of cementoplasty of periacetabular lesions are unknown. We performed multimodal biomechanical testing to address this question. We find improved strength, resilience and acetabular protection with the technique. The results recommend this novel technique as a preferred surgical option.